A micro level investigation of stakeholder motives on university technology transfer business models. Issue 5 (4th May 2021) - McAdam, Maura; Miller, Kristel; McAdam, Rodney
ABSTRACT: Within this paper, we take a micro level perspective to explore how ecosystem stakeholder motives have impacted value creation and value capture processes within the University Technology Transfer (UTT) business model over time. To achieve this, we adopt a longitudinal qualitative methodology comprising of case study evidence of two differing bounded contexts of universities and their respective UTT stakeholder-based business models over an eight-year period. Our findings reveal, that in seeking to balance and align the value creation and capture processes needed to satisfy diverse stakeholders and achieve university mission, the importance of portfolio models within UTT business model design to ensure ongoing strategic alignment and sustainability.